2011
DOI: 10.1128/aac.01695-10
|View full text |Cite
|
Sign up to set email alerts
|

Connection Domain Mutations in HIV-1 Reverse Transcriptase Do Not Impact Etravirine Susceptibility and Virologic Responses to Etravirine-Containing Regimens

Abstract: Connection domain mutations (CDMs) in HIV-1 reverse transcriptase (RT) alter susceptibility to some nucleoside/nonnucleoside RT inhibitors (NRTIs/NNRTIs). Their effects on susceptibility and virologic responses to etravirine were analyzed. Seventeen CDMs were evaluated: L283I, E312Q, G333D, G333E, G335C, G335D, N348I, A360I, A360T, A360V, V365I, T369I, A371V, A376S, I393L, E399D, and E399G. CDM prevalence and effects on virologic responses were analyzed retrospectively using clinical data. The effects on etrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 28 publications
2
29
1
Order By: Relevance
“…Previous studies showed that N348I can increase resistance to ETR (29,97,98). Now, we also show that N348I can enhance resistance to both ETR and RPV if E138K is also present.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies showed that N348I can increase resistance to ETR (29,97,98). Now, we also show that N348I can enhance resistance to both ETR and RPV if E138K is also present.…”
Section: Discussionsupporting
confidence: 53%
“…A less common CN amino acid change, T369I, was observed in conjunction with Y181C in one of our phenotypically resistant patient samples. Previous publications have shown that T369I can influence EFV, NVP, and ETR susceptibility in subtype B (62,63). Reconstruction of the mutations in p8.MJ4 demonstrated that T369I significantly decreased susceptibility to all NNRTIs in subtype C, including RPV, when it occurred in combination with Y181C.…”
Section: Discussionmentioning
confidence: 99%
“…As a diarylpyrimidine, ETR has a high capacity for isomerization, which allows it to effectively bind to and inhibit common mutated forms of the viral enzyme (Andries et al, 2004;Vingerhoets et al, 2005;Gupta et al, 2011;Picchio et al, 2011). Therefore, ETR has a higher genetic barrier to viral resistance and as such is often prescribed for treatment-experienced patients who have developed mutations that confer resistance to first-generation NNRTIs (Lazzarin et al, 2007;Madruga et al, 2007;Nadler et al, 2007).…”
Section: Introductionmentioning
confidence: 99%